The Effect of Combining Video Lectures and Kolb Experiential Learning on EFL Student-Teachers’ Ability to Teach Communicative Coursebook and their Teaching Competencies (Journal of the College of Education for Women, 2019)
Communicative-based textbooks are developed and disseminated throughout the country.However, it is difficult for teachers who themselves have learnt English through the traditionalapproaches to suddenly be familiar with CLT (Communicative Language Teaching) principlesand teach communicatively. Therefore, many teachers remain somewhat confused about whatexactly CLT is and others familiar with CLT but unable to achieve communicative classroomteaching. Consequently, those teachers need to be introduced to the CLT principles and they needtraining in how to put CLT principles into practice. Accordingly, this study aims to find out theeffect of combining video lectures and Kolb experiential learning on EFL student-teachers’ability to teach communicative course book and their teaching competencies (Subject matterscompetency (knowledge) Professional competency (Skills), and Personal competency (attitude)).The sample is represented by (46) fourth year student-teachers at English department/eveningstudies/ College of Education for Women/University of Baghdad, one of the two groups of (23)student- teacher is selected as experimental group and the other as control group. Anobservational checklist is constructed to achieve the aim of the study. After exposing theexperimental group to the video lectures combined with experiential learning phases for trainingand exposing the control group to teacher- centered lectures about the teaching competenciesfollowed by their microteaching to get feedback and then both groups are assessed by the studyinstrument. The results of the study show that the combining of video lectures and experientiallearning has an effect on the experimental group’s ability to teach communicative course bookand their teaching competencies. Based on the results, recommendations and suggestions forfurther studies are put forward.